The British naval staff in the First World War - Black, Nicholas (Boydell Press, 2009)
Nicholas Black examines the role of the Naval Staff of the Admiralty in the 1914-18 war, reassessing both the calibre of the Staff and the function and structure of the Staff. He challenges historians such as Arthur Marder and naval figures such as Captai.